Strategic diagnosis of a property specialized in breeding, rearing and finishing beef cattle in the southern region of Piauí - Silva, Rosemeire Pereira da; Fernandes, ArturHenriqueSousa; Carneiro, Priscila Teixeira de Souza; Gurgel, Antonio Leandro Chaves; Santos, Viviany Lúcia Fernandes dos (Acta Scientiarum. Animal Sciences, 2022)
This study aimed to perform a strategic diagnosis on a property specialized in breeding, rearing and finishing beef cattle in the southern region of Piauí. It was conducted at Agropecuária Alvorada, located in the countryside, municipality of Bom Jesus, PI, Brazil. The farm develops the full cycle of beef cattle production, which is divided into breeding, rearing and finishing. A SWOT analysis (which stands for Strengths, Weaknesses, Opportunities and Threats) was carried out, consisting of an assessment of the property’s internal and external environments. To evaluate the internal environment, an interview was held for data collection by means of questionnaires. The evaluation included: breeding management, sanitary management, nutritional management, infrastructure, workforce, technologies used in pasture formation, conservation and recovery, pasture management and zootechnical indices. To analyze the external environment, a group of people (experts) with deep knowledge of the subject addressed during the study was used as source of information. A matrix was generated with all the information from the SWOT analysis, strengths, weaknesses, opportunities and threats, culminating with the establishment of strategies to increase the productive efficiency of the cattle raising activity.